2011
DOI: 10.1017/s1368980011001376
|View full text |Cite
|
Sign up to set email alerts
|

Validity of an adapted Household Food Insecurity Access Scale in urban households in Iran

Abstract: Objective: To assess the validity of a locally adapted Household Food Insecurity Access Scale (HFIAS) in the measurement of household food insecurity (FI) in the city of Tehran. Design: A cross-sectional study. Setting: Urban households were selected through a systematic cluster sampling method from six different districts of Tehran. The socio-economic status of households was evaluated using a questionnaire by means of interviews. An adapted HFIAS was used to measure FI. Content validity was assessed by an ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
92
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 28 publications
13
92
5
Order By: Relevance
“…In this population, where severe food insecurity was not highly prevalent, it is possible that participants projected their own experience with food insecurity on the understanding of the term 'worry', thereby interpreting it as more related to quality rather than absolute quantity. Our results showed that the Arabic version of the HFIAS has a comparable internal consistency (Cronbach's a 5 0?91) to that previously reported for the Tanzanian and Iranian versions of the questionnaire (Cronbach's a 5 0?90 and 0?85, respectively) (14,15) .…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…In this population, where severe food insecurity was not highly prevalent, it is possible that participants projected their own experience with food insecurity on the understanding of the term 'worry', thereby interpreting it as more related to quality rather than absolute quantity. Our results showed that the Arabic version of the HFIAS has a comparable internal consistency (Cronbach's a 5 0?91) to that previously reported for the Tanzanian and Iranian versions of the questionnaire (Cronbach's a 5 0?90 and 0?85, respectively) (14,15) .…”
Section: Discussionsupporting
confidence: 76%
“…Correlations of the HFIAS scores with poverty and lower education levels lent support for its validity, as previous reports also showed food insecurity to be negatively associated with markers of wealth (1,14) .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…However, the inclusion of IFIAS items 5 and 6 together with items 2-4 in the same grouping is novel to our study. Reports by Mohammadi et al (29) using data from Iran and by Kneuppel et al (27) using data from rural Tanzania indicated that item 5 grouped together with HFIAS items 1-4 while item 6 grouped with items 7-9. In the study by Kneuppel et al, the factor loading for item 6 in each of their two emergent factors was above their selected cut-off of 0·5, indicating that potentially HFIAS item 6 can group with HFIAS items 1-5, as was observed in our study.…”
Section: Discussionmentioning
confidence: 98%